Os processos educativos e a construção identitária dos jovens agricultores do município de Vacaria (RS) - Fischer, Eveline (My University, 2020)
This research had as object of study the educational processes and the identity construction of the young farmers of Vacaria - RS. The main objective of the study consists of investigating the influences of school and non-school educational processes on youth identity construction represented by small family farmers of Vacaria. The theoretical framework sought to conceptualize what is understood by plural youths, identity construction, and school and non-school education, from authors such as Pais (1990; 2003), Sposito (1997; 2002; 2003; 2018), Carneiro (1998; 2007 ; 2008), Castro (2009; 2016); Hall (2006); Brandão (1984; 2007), Freire (1996, 2017), among others. A textual discursive analysis proposed by Moraes and Galiazzi (2007) was used as a method after transcripts of semi-structured interviews conducted with five young people between 15 and 29 years old. The narratives of the young emerged categories that fit into five themes: 1) Intrafamily relationships and conditionality of the profession; 2) The difficult task to identify different identities: being young, being a farmer and being a student; 3) School knowledge and declaration of identity of the farmer; 4) Establishment of a collaborative network: non-school education; and 5) The social commitment of agriculture. The research results show that there are applicable contributions, but also the school and non-school educational processes in the identity construction of young people. The fact that they had born in farming families makes them automatically enter the profession and have their first formation, learning early how to work on land by observing and reproducing adult forms of work. However, to overcome the initial role of helper until reinforcing the identity of the farmer, with autonomy to work in the profession, was recorded a long period of time that is still being covered by most respondents. For them, the sense of belonging and appreciation of the rural environment must be reinforced by the elementary school, while the technical knowledge necessary to be autonomous in their professions is attributed to higher or technical education. Access to the systematized knowledge is understood as a form of emancipation for young people. But they do face several limitations in identifying their identities as young people, students, and farmers when different meanings confront each other in their narratives. The experience of youthful loneliness is verified when no definitions are applied in the development of the profession by other young people in their communities. Finally, they report to seek mechanisms to address the lack of school education, meet their demands and complement the school of life, in training offered by syndicate of agricultural workers and Emater.
A pesquisa teve como objeto de estudo os processos educativos e a construção identitária dos jovens agricultores do município de Vacaria (RS). O objetivo principal do estudo consistiu em investigar as influências dos processos educativos escolares e não escolares na construção identitária da juventude representada por pequenos agricultores familiares de Vacaria. O referencial teórico buscou conceituar o que se entende por juventudes plurais e construção identitária, além de educação escolar e não escolar, a partir de autores como Pais (1990; 2003), Sposito (1997; 2002; 2003; 2018), Carneiro (1998; 2007; 2008), Castro (2009; 2016); Hall (2006); Brandão (1984; 2007) e Freire (1996; 2017), entre outros. A análise textual discursiva proposta por Moraes e Galiazzi (2007) foi utilizada como metodologia após as transcrições das entrevistas semi-estruturadas realizadas com cinco jovens entre 15 e 29 anos de idade. As narrativas dos jovens fizeram emergir categorias que se encaixaram em cinco diferentes temas: 1) Relações intrafamiliares e a condicionalidade da profissão; 2) A difícil tarefa de conciliar diferentes identidades: ser jovem, ser agricultor e ser estudante; 3) O conhecimento escolar e a afirmação da identidade do agricultor; 4) Estabelecendo uma rede de colaboração: o ensino não escolar; e 5) O compromisso social da agricultura. Os resultados da pesquisa mostraram que existem contribuições significativas, mas também limitações dos processos educativos escolares e não escolares na construção identitária dos jovens. O fato de terem nascido em famílias agricultoras fez com que se inserissem automaticamente na profissão e tivessem as suas primeiras experiências formativas, aprendendo desde cedo o trabalho na terra pela observação e reprodução das formas de trabalho dos adultos. Porém, para superar o papel inicial de ajudante até a consolidação da identidade de agricultor, com autonomia para atuar na profissão, foi verificado um longo trajeto que ainda está sendo percorrido pela maioria dos entrevistados. Para eles, o sentimento de pertença e valorização do meio rural deve ser reforçado pela escola básica, enquanto que os conhecimentos técnicos necessários para serem autônomos em suas profissões são atribuídos ao ensino superior ou técnico. O acesso ao saber sistematizado é entendido como uma forma de emancipação para os jovens. Mas revelam enfrentar inúmeras limitações para conciliarem suas identidades de jovens, estudantes e agricultores quando diferentes significados se confrontam em suas narrativas. É verificada a vivência de uma solidão juvenil quando não encontram referências no desenvolvimento da profissão por outros jovens em suas comunidades. Por fim, relatam buscar mecanismos para suprir a falta da educação escolar, atender as demandas diárias e complementar a escola da vida, em formações oferecidas pelo sindicato dos trabalhadores rurais e pela Emater.
Keywords: Educação; Identidade; Juventude; Trabalhadores rurais - Vacaria (RS); Education; Identity; Youth; Agricultural laborers - Vacaria (Brazil)